MANAJEMEN KEPALA MADRASAH DALAM MENGEMBANGKAN MUTU PENDIDIKAN (STUDI DI MTS DARUL FALAH CERMEE BONDOWOSO) - Ahmad Sarwini; Abdul Haq As; Khoirul Ulum; Muhammad Abrori (Hijri, 2026)
Educational quality is a primary indicator of the success of educational implementation in madrasahs. The head of the madrasah plays a strategic role as a manager, leader, and the main driving force in the development of educational quality. This study aims to analyze the management of the madrasah head in developing educational quality at MTs Darul Falah Cermee Bondowoso, focusing on the aspects of planning, implementation, and evaluation. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation. The findings reveal that: (1) educational quality planning is conducted participatively through the preparation of the Madrasah Work Plan (RKM) and the development of flagship programs based on Islamic values; (2) the implementation of quality development is realized through the leadership of the madrasah head by integrating the EMASLIM functions and strengthening a religious culture within the madrasah environment; and (3) quality evaluation is carried out continuously through internal monitoring mechanisms, teacher performance evaluation, and program reflection. This study confirms that the integration of modern educational management and Islamic values is the key to the successful development of madrasah educational quality